A fine imitation : a novel - Brock, Amber (New York : Crown Publishers, 2016)
Enduring a life of lonely desperation in spite of her beauty, pedigree, and Park Avenue penthouse, Vera is drawn to a secretive French artist who is painting a mural in her coveted building, a relationship that reminds her about a talented forger from her past who nearly cost her everything.
Keywords: Socialites -- Fiction; Painters -- Fiction; Friendship -- Fiction; Self-realization -- Fiction; Painters; Socialites; Literary -- Fiction; Manhattan (New York, N.Y.) -- Fiction; New York (State) -- New York -- Manhattan; Fiction; Historical fiction; Romance fiction; Love stories; Historical fiction; Romance fiction; Historical fiction